Studies on the structural property, mechanical relationships and corrosion behaviour of Inconel 718 and SS 316L dissimilar joints by TIG welding without using activated flux. (December 2017) - Ramkumar, T.; Selvakumar, M.; Narayanasamy, P.; Begam, A. Ayisha; Mathavan, P.; Raj, A. Arun
Abstract: This research article addresses about the joining of 4 mm thick plates of Inconel 718 and ferritic stainless steel (S.S) 316L by Tungsten Inert Gas (TIG) welding process without using the activated flux. Trial experiments were conducted to find the influence of welding current on the depth of penetration and depth to width (D/W) ratio. The studies proved that a complete penetration could be achieved in multi pass. Microstructure examination using optical and Scanning Electron Microscope (SEM) clearly exposed the development of unmixed zone and also the Heat Affected Zone (HAZ) of Inconel 718. The chemical components of the Inconel 718 and SS316L were determined using Energy Dispersive Analysis (EDAX). Tensile and bend failures were observed at the parent metal of Inconel 718, SS316L and Inconel 718 & SS316L dissimilar joints. It was indicated from the notch tensile studies that the notch strength ratio was better than unity, which established that the weldments were ductile in all circumstances. The corrosion studies were carried out in the Nacl solution and it was found that Inconel 718 and SS316L dissimilar joint possess less corrosion resistance than similar SS316L weldment. It was inferred from the current study that the ultimate tensile strength of dissimilar weldments was better compared to similar weldments and the failure was observed in the parent metal for all the cases. Bend test results portrayed that dissimilar weldments possess better strength compared to SS316L weldments.